2007
DOI: 10.1177/1748048507082842
|View full text |Cite
|
Sign up to set email alerts
|

National Influences in Foreign News

Abstract: / This article examines the impact of national influences and national interests upon foreign news coverage. To this end, it examines the newspaper reporting on the 12 November 1991 `Dili Massacre', a case study neglected by academic research and press coverage analysis. This work introduces the distinction between intra-media and extra-media influences while looking at nuanced dimensions regarding the source of national influences on the basis of differences between the press and government agendas as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…National interests relate to the political, economic, militarist, sociocultural, and security objectives of a country and comprise value choices by policymakers to minimize costs and to maximize benefits for the good of the country (Li, 2003). Journalists employ national interest frames by explicitly highlighting or making implicit assumptions about these objectives and value choices to explain an event or issue and to resonate with domestic audiences (Brewer, 2006; Novais, 2007). In this manner, media reduce the complexity of foreign cultures (Said, 1993) and impose elite-defined national interests and agendas onto international matters (Akhavan-Majid and Ramaprasad, 1989; Dorogi, 2001).…”
Section: Literature Reviewmentioning
confidence: 99%
“…National interests relate to the political, economic, militarist, sociocultural, and security objectives of a country and comprise value choices by policymakers to minimize costs and to maximize benefits for the good of the country (Li, 2003). Journalists employ national interest frames by explicitly highlighting or making implicit assumptions about these objectives and value choices to explain an event or issue and to resonate with domestic audiences (Brewer, 2006; Novais, 2007). In this manner, media reduce the complexity of foreign cultures (Said, 1993) and impose elite-defined national interests and agendas onto international matters (Akhavan-Majid and Ramaprasad, 1989; Dorogi, 2001).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The national interest of any medium's home country is one of the major factors, which influences media coverage when news media and their journalists cover international issues (Lee & Yang, 1995;Lee et al, 2005;Novais, 2007). Thus, given that the 2008 U.S. election was crucial to the national interests of South Korea, it was not surprising that South Korean journalists would also consider both the FTA between the U.S. and South Korea and U.S. policy towards North Korea to be important issues, which were very relevant to their nation and its people.…”
Section: Research Question and Hypothesismentioning
confidence: 99%
“…Researchers have described a variety of factors that influence framing of international news (Brewer, 2006;Fang, 2001;Jang, 2013;Kim, 2000;Novais, 2007;Lee and Yang, 1996;Nossek, 2004;Seo, 2009;Wang, 1995;Yang, 2003Yang, , 2008Zhang and Fleming, 2005). Several studies have shown that dominant ideology and national interests are primary factors that influence news framing (Becker, 1984;Massey, 2000;Verschueren, 1985;Wang, 1991).…”
Section: International News and Framesmentioning
confidence: 99%
“…Scholars argue that national interest is a main factor that explains the difference in international news coverage (Lee and Yang, 1996; see also Novais, 2007). Brewer (2006) took an experimental approach to examining the relationship between national interest frames in media coverage and public opinion about world affairs.…”
Section: International News and Framesmentioning
confidence: 99%